2018
DOI: 10.22266/ijies2018.0630.22
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Framework for Effort Estimation of Agile Projects

Abstract: Software effort estimation methods are used to measure the total time and forecast the amount of required effort to develop the software. In addition, agile software projects, the requirements are characterized by changeability during the software projects. Therefore using the traditional estimation models in agile software projects may cause inaccurate effort estimation. This paper proposes a framework which utilizes The Constructive Cost Model (COCOMO II), story points, and fuzzy logic models without affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Raslan and Darwish [24] proposed a system based on mixing the story point. The authors used magnitude relative error (MRE) and percentage relative error deviation (PRED) for evaluation purposes.…”
Section: Related Workmentioning
confidence: 99%
“…Raslan and Darwish [24] proposed a system based on mixing the story point. The authors used magnitude relative error (MRE) and percentage relative error deviation (PRED) for evaluation purposes.…”
Section: Related Workmentioning
confidence: 99%
“…The main issue of determining EE in agile methods is to focus on the effort and degree of difficulties of teamwork rather than an individual [10]. Some of the existing work showed that while using ASD, development team used story point approach [11] to calculate the effort with the help of user story and project velocity as inputs. The main task is to estimate the required effort to reduce the technical complexity of the project.…”
Section: Introductionmentioning
confidence: 99%